Is flexible sigmoidoscopy screening associated with reducing colorectal cancer incidence and mortality? a meta-analysis and systematic review - Wang, Xinmiao; Cao, Luchang; Song, Xiaotong; Zhu, Guanghui; Ni, Baoyi; Ma, Xinyi; Li, Jie (Frontiers in Oncology, 2023)
The question of whether flexible sigmoidoscopy (FS) for colorectal cancer (CRC) affects incidence or mortality remains unclear. In this study, we conducted a meta-analysis and systematic review to explore this issue.2 Methods: A systematic search of PubMed, EMBASE, and ClinicalTrials.gov was performed for cohort studies (CS), case-control studies, and randomized controlled trials (RCTs) of people who underwent FS and reported mortality or incidence of CRC until December 11, 2022. Relative risk (RR) was applied as an estimate of the effect of interest. To combine the RRs and 95% confidence intervals, a random-effects model was used. The quality of the included studies and evidence were assessed by Newcastle-Ottawa quality assessment scale, the Jadad scale, and "Grading of Recommendations Assessment, Development and Evaluation System".Results: There were a total of six RCTs and one CS, comprising 702,275 individuals.FS was found to be associated with a 26% RR reduction in CRC incidence (RR, 0.74; 95% CI, 0.66-0.84) and a 30% RR reduction in CRC mortality (RR, 0.70; 95% CI, 0.58-0.85). In the incidence subgroup analysis, FS significantly reduced the incidence of CRC compared to non-screening, usual care, and fecal immunochemical testing.Significance was also shown in men, women, distal site, stage III-IV, age of 55-59, and age over 60. In terms of the mortality subgroup analysis, the results were roughly the same as those of incidence.According to this study, FS might reduce the incidence and mortality of CRC. To confirm this finding, further prospective clinical studies should be conducted based on the larger-scale population.Trial registration: PROSPERO registered number : CRD42023388925.